Recent Advances in Cr-Catalyzed Asymmetric Nozaki–Hiyama–Kishi Reaction: From Alkyl Electrophiles to Alkyl Nucleophiles - Shen, Haigen; Zhang, Feng-Hua; Wang, Zhaobin (Synthesis)
The Nozaki-Hiyama-Kishi (NHK) reaction is renowned for its excellent chemoselectivity and functional group compatibility in carbonyl additions, and has been widely applied in natural product synthesis. However, its development remained relatively dormant for a long time, largely due to limitations such as the limited diversity of radical precursors, the narrow structural diversity of products, and the need for stoichiometric metal reductants and dissociation reagents.Recently, the reaction has witnessed significant progress, driven by advances in asymmetric radical chemistry as well as photo-and electrochemistry. In this review, we summarize key developments in chromium-catalyzed asymmetric NHK reactions over the past decade, covering substrate scope, stereocontrol, and mechanistic insights, and discuss the opportunities and challenges that remain in this field.